2020
DOI: 10.1038/s41598-020-63104-6
|View full text |Cite
|
Sign up to set email alerts
|

A multivariable Mendelian randomization to appraise the pleiotropy between intelligence, education, and bipolar disorder in relation to schizophrenia

Abstract: MR-egger intercept. While inverse-variance weighted (IVW) column provides the main MR results in

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(55 reference statements)
1
8
2
Order By: Relevance
“…risk exposures such as trauma). Contrasting our findings, previous MR estimates using earlier schizophrenia GWASs hint at an increased risk for schizophrenia per additional year of education 26,28 , as we found for anorexia, OCD, and bipolar disorder.…”
Section: Schizophreniacontrasting
confidence: 99%
“…risk exposures such as trauma). Contrasting our findings, previous MR estimates using earlier schizophrenia GWASs hint at an increased risk for schizophrenia per additional year of education 26,28 , as we found for anorexia, OCD, and bipolar disorder.…”
Section: Schizophreniacontrasting
confidence: 99%
“…To some extent, driving speed reflects intelligence and cognitive status [ 71 , 72 ]. Previous MR study has reported that higher intelligence was causally associated with lower SCZ risk [ 73 ]. The observed association between automobile speeding propensity and SCZ risk might be mediated with intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…It is also in line with studies using genetically informed methods, finding positive associations between polygenic risk for educational attainment and schizophrenia, 27 although other studies have reported associations in the opposite direction. 28 In order to further elucidate this issue, causal inference methods such as Mendelian randomization have been applied, shedding more light on the complex relation between educational attainment, schizophrenia and intelligence, 29 , 30 although without reaching a final conclusion.…”
Section: Discussionmentioning
confidence: 99%